Outcomes in surgical management of sinonasal malignancy—A single comprehensive cancer center experience. Issue 4 (25th January 2022) - Adilbay, Dauren; Valero, Cristina; Fitzgerald, Conall; Yuan, Avery; Mimica, Ximena; Gupta, Piyush; Wong, Richard J.; Shah, Jatin P.; Patel, Snehal G.; Ganly, Ian; Cohen, Marc A.
Abstract: Background: Sinonasal malignancies are a complex and diverse group of tumors. Over the past five decades, treatment advances have changed the management paradigms for these tumors. Our aim was to analyze the outcomes of patients from a comprehensive cancer center. Materials and Methods: We retrospectively assessed 400 patients with sinonasal malignancies treated with surgery at our center between 1973 and 2015. Multiple variables were reviewed to assess the influence on 5‐year outcomes. Results: The median age was 56 years (IQR 46.8–68). Two hundred and fifty‐nine (65%) were males and 141 (35%) were females. Overall survival (OS) and disease‐specific survival (DSS) improved in the last analyzed decade. Orbital invasion, advanced pT‐classification and pN‐classification, and melanoma histology were associated with poorer outcomes. Conclusion: Treatment outcomes for patients with sinonasal malignancy have improved over time. This is likely multifactorial with advances in surgical technique, adjuvant treatment, and patient selection. pT‐classification, pN‐classification, orbital invasion, and histology are predictive of survival.